The Inhibitory Effect of Gallic Acid on Human Serum Cholinesterase - M.K. Al-Shafi, Sabah; J.Al-Azzaw, Mohamed; A. Ali, Methal (Iraqi Journal of Pharmaceutical Sciences, 2017)
The dried fruit peel of pomegranate in Punicaceae family was fractionated chromatographically on Sephadex-LH-20 column .Gallic acid (trihydroxybenzoic acid) and its related galloyl esters such as gallotannin(i.e. β-penta-O-galloyl–D-glucose) were obtained homogenously. Different concentrations of gallic acid and gallotannin were used to determine their inhibitory effect on human serum cholinesterase. The enzyme activity was measured according to the method reported by the WHO .The inhibitory effect of these compounds on the activity of human serum cholinesterase have been studied in vitro .The inhibitory effect was remarkably clear with increasing concentration of gallic acid .Whereas galloyl ester showed no inhibitory effect. The inhibition with gallic acid indicates a noncompetitive pattern. Therefore, we can not recommended gallic acid and its related compounds , as preservative substances in food industry or in pharmacological preparations since they might have some side effect on certain biological systems.. Key words: Gallic acid , gallotannin , Human Serum Cholinesterase .